Earthen construction technology : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France), volume 11, session V - Daneels, Annick,; Torras Freixa, Maria, (UISPP proceedings series ;, 2021)
Presents papers from Session IV-5 of the 18th UISPP World Congress (Paris, June 2018). The archaeological study of earthen construction has until now focused on typology and conservation; papers here instead consider their construction and anthropological importance.